Fatigue Strength of Steel Members with Welded Details (T.R. Higgins Award) - Fisher, John W.; Yen, Ben T. (Engineering Journal, 1977)
Early studies on the fatigue of welded steel structures and components revealed the influencing factors such as stress magnitudes and geometry of structural details. Approximate design relationships were developed in the 1940s and, overall, very few problems occurred with steel bridges and structures as a result of fatigue. The fatigue cracking of coverplated steel beam bridges of the AASHO Road Test3 in the early 60s led to further examinations of the controlling factors and more extensive studies. A substantial amount of experimental data has been developed on steel beams since 1967 from a study sponsored by the National Cooperative Highway Research Program (Project 12-7) and carried out at Fritz Laboratory, Lehigh University. These studies have shown that the most important factors which govern the fatigue strength are the stress range and the type of details. For each type of welded structural detail, regardless of the strength of the steel, the applied stress range was found to cause propagation of fatigue cracks from initial discontinuities at the details. The fatigue life of a detail was nearly exhausted when the crack had propagated through the thickness of the flange plate. These findings were observed to be applicable to rolled beams, welded beams, beams with groove-welded flange splices, coverplated beams, and to beams with welded stiffeners and attachments. Comprehensive specifications based on stress range alone have been developed for bridge and building structures 6-8 utilizing these beam test data and other available information in the literature. This paper reviews very briefly the governing parameter of stress range, the experimental results on welded stiffeners and attachments, the phenomenon of crack propagation, and the data basis for the specifications. In addition, some secondary considerations which have caused fatigue cracking are examined and possible ways of retrofitting cracked structural details are suggested.